Assessment and measurement bias in madrasa performance evaluation: Evidence from underdeveloped areas in Indonesia - Eko Wahyunanto Prihono; Ridhwan Latuapo; Fitria Lapele; Siti Irene Astuti Dwiningrum; Janu Arlinwibowo; Margarito Surbito Reyes Jr. (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
Inequality is a condition characterized by an unbalanced assessment process. Physical and psychological factors, both those measuring and those being measured, may impact assessment inequality. The purpose of this research was to highlight the potential inequity in the performance assessment of madrasas in underdeveloped areas. A quantitative research design was employed. The data were collected using a questionnaire instrument that had been proven valid and reliable. Path analysis was used to determine both direct and indirect effects. The findings showed that measurement errors related to the instruments used have a direct positive effect on inequality in the performance assessment of madrasas in underdeveloped areas, as well as an indirect effect mediated through teacher quality. One alternative solution to reducing the imbalance in assessing the performance of madrasas in underdeveloped areas can be implemented through policy dimensions, including macro, meso, and micro dimensions.